Dakwah Strategy for Special Recidivist Inmates Against Changes in Convict Behavior - Faiz, Faiz; Saifillah, Muhammad; Farhan, Farhan (JURNAL ISLAM NUSANTARA, 2022)
This study was conducted to understand the strategies used by prison officers in providing da'wah to inmates, especially to recidivists at the Class II B Detention Center Kraksaan, Probolinggo, East Java. This study used qualitative research methods. In collecting data and information, the researcher made observations first, then conducted interviews with several informants using the purposive sampling technique. The results of the study show that; the da'wah strategy is carried out by prison officers to inmates using three strategies; First, the educational da'wah strategy from this strategy, there are many educational activities and activities, such as recitation of books, counseling, reading the Koran. Second, da'wah bil al-hal, with refraction to the goodness exemplified by the officers. The third strategy is cultural da'wah; this da'wah guides the form of development skills and skills which are expected to be helpful when leaving the detention house later.